Membangun Harmoni di Desa Lilangan Melalui Kegiatan Gebyar Muharram - Utami, Atikah Dewi; Roihana, Ihda; Asis, Febhia Zenia; Al-Husni, Asma (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
Muharram Festival activities are held to increase community unity and harmony in facing plural social conditions which have the potential to become conflict in the future, by uniting people in one place using the concept of social integration. Social integration is intended as a process of adjustment to understand each other, accept situations, views and actions in a harmonious social life order so that conflict does not occur. Among the expected goals is that for the community, celebrating it can be a good moment to unite the community to become more harmonious. For the children who take part in the competition, this activity is a motivation and encouragement for the children to learn Islamic values. Religiously, this activity is a medium for da'wah in broadcasting the Islamic New Year to be more meaningful.